Applying the Theory of Planned Behavior to Study the Online Entrepreneurship Intentions among Women in Rural Areas of Vietnam - Hong Minh Ngoc Tran; Duy Vu Le (Migration Letters, 2023)
This study adopts the Theory of Planned Behavior (TPB) model to examine and assess the influence of TPB factors on the online entrepreneurial intention of women residing in rural areas of Vietnam. The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique is employed, utilizing data collected from 263 women in rural Vietnam. The findings reveal that Attitude, Subjective norm, Perceived behavioral control, and Knowledge support significantly impact women’s intention to engage in online entrepreneurship. Notably, Knowledge support emerges as the strongest determinant among these factors, exerting the most substantial influence on women’s online entrepreneurial intention.